2014
DOI: 10.1016/j.visres.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Similarity-based distortion of visual short-term memory is due to perceptual averaging

Abstract: A task-irrelevant stimulus can distort recall from visual short-term memory (VSTM). Specifically, reproduction of a task-relevant memory item is biased in the direction of the irrelevant memory item (Huang and Sekuler, 2010a). The present study addresses the hypothesis that such effects reflect the influence of neural averaging under conditions of uncertainty about the contents of VSTM (Alvarez, 2011; Ball and Sekuler, 1980). We manipulated subjects’ attention to relevant and irrelevant study items whose simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 42 publications
6
61
1
Order By: Relevance
“…If recently memorized information can bias current processing, then serial dependence might operate regardless of whether stimuli are serially presented across trials or within a trial. Accordingly, Huang and Sekuler () found that the spatial frequency of a Gabor stimulus was attracted towards the spatial frequency of a previously presented Gabor also when both stimuli were encoded within a trial (see also Dubé, Zhou, Kahana, & Sekuler, ). Strikingly, two recent studies found a repulsive instead of attractive bias, thus pointing at a different mechanism of serial dependence.…”
Section: Introductionmentioning
confidence: 99%
“…If recently memorized information can bias current processing, then serial dependence might operate regardless of whether stimuli are serially presented across trials or within a trial. Accordingly, Huang and Sekuler () found that the spatial frequency of a Gabor stimulus was attracted towards the spatial frequency of a previously presented Gabor also when both stimuli were encoded within a trial (see also Dubé, Zhou, Kahana, & Sekuler, ). Strikingly, two recent studies found a repulsive instead of attractive bias, thus pointing at a different mechanism of serial dependence.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, subjects’ reproductions of the spatial frequency of the remembered stimulus yield a sensitive, trial-by-trial continuous measure of accuracy. This information-rich measure of accuracy made it possible not only to gauge whether there was an error in memory, but more importantly to gauge the degree to which errors reflected the influence of the task-irrelevant stimulus (Dube, Zhou, & Sekuler, under review; Huang & Sekuler, 2010b). Many factors during each trial may contribute to the total error including pure error of reproduction, but, as explained below, the use of Gabor stimuli and the recall technique made it possible to disentangle the influence of other stimuli seen during the experiment, particularly each trial’s nonTarget stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…When the observer is tested regarding the identity of an object from a given spatial position, there may be some probability that the observer makes the judgment with respect to an item from the wrong position (e.g., Bays et al, 2009;Donkin, Tran, & Pelley, 2015;Dubé, Zhou, Kahana, & Sekuler, 2014). One approach to addressing this issue is to conduct paradigms in which the observer is presented with only a single object from a single spatial position on each trial.…”
Section: Methodsmentioning
confidence: 99%